Peningkatan Pengetahuan dan Keterampilan Ibu-Ibu PKK Kelurahan Lubuk Durian melalui Penyuluhan dan Pelatihan Pemanfaatan Nasi Sisa Menjadi Pupuk Organik Cair - Raisawati, Tatik; Sumarni, Hania; Supriyanti, Yuni Indah (Universitas Nusantara PGRI Kediri, 2023)
Lubuk Durian Village is a village located in Kerkap District, North Bengkulu Regency, Bengkulu Province. The emergence of the COVID-19 pandemic has an impact on the activities carried out by the community. PKK women in Lubuk Durian Village are very enthusiastic about finding useful activities to do during the pandemic. One of the activities of interest is processing waste into something useful. One of the items that are considered waste from daily life activities is leftover rice. Leftover rice is usually thrown away by PKK women in Lubuk Durian Village. This community service activity aims to provide information and improve the knowledge and skills of PKK mothers in Lubuk Durian Village. This activity is carried out using counseling methods and product manufacturing training. The results obtained from this PkM activity are that PKK women in Lubuk Durian Village get knowledge and skills on how to handle leftover rice so that it can be useful, namely by making it as liquid fertilizer. This activity can be used to foster a sense of empathy and responsibility for the environmental community